Inactive rhomboid proteins: New mechanisms with implications in health and disease - Lemberg, Marius; Adrain, Colin (Seminars in cell & developmental biology, 2016)
Rhomboids, proteases containing an unusual membrane-integral serine protease active site, were first identified in Drosophila, where they fulfill an essential role in epidermal growth factor receptor signaling, by cleaving membrane-tethered growth factor precursors. It has recently become apparent that eukaryotic genomes harbor conserved catalytically inactive rhomboid protease homologs, including derlins and iRhoms. Here we highlight how loss of proteolytic activity was followed in evolution by impressive functional diversification, enabling these pseudoproteases to fulfill crucial roles within the secretory pathway, including protein degradation, trafficking regulation, and inflammatory signaling. We distil the current understanding of the roles of rhomboid pseudoproteases in development and disease. Finally, we address mechanistically how versatile features of proteolytically active rhomboids have been elaborated to serve the sophisticated functions of their pseudoprotease cousins. By comparing functional and structural clues, we highlight common principles shared by the rhomboid superfamily, and make mechanistic predictions.
Gesehen am 25.06.2020